Halogen Cations - Morton, Michael John (My University, 1969)
In an investigation on the formation of halogen cations, the I4 2+, Br3+, Br2+ and Cℓ3+ cations have been identified by conductivity, cryoscopy, ultraviolet and visible spectrophotometry, Raman spectroscopy and magnetic susceptibility measurements in strong acids. Bromine trifluorosulphate has been shown to ionise in the SbF5:3SO3/HSO3F system to give the Br(SO3F)2+ ion, and Raman bands of bromine fluorosulphates, CℓSO3F and S2O6F2 have been listed. No evidence has been found for the Cℓ2+ or CℓF+ ions in solution, and the assignment of observed ESR spectra to these cations is criticised.
Raman spectra of the adducts AsF5 2CℓF and BF3 2CℓF have shown that they contain the CℓCℓF+ cation and not the CℓFCℓ+ cation. The bending frequency of the CℓF2+ cation has been reassigned, and force constants have been calculated for the CℓF2+ and Cℓ3+ cations.
Resonance Raman spectra of the I2+ and Br2+ cations have been observed, and, as few examples of this effect are known, the variation in fundamental and overtone intensities with exciting wavelength have been investigated.
Keywords: halogen, cations, acids, force, magnetic